JENIS MATERIAL PAHAT POTONG DAN RUN OUT TERHADAP KEKASARAN PERMUKAAN BENDA KERJA SILINDER PADA PROSES BUBUT - Hendra, Hendra; Sutarmadi, Sutarmadi; Indriani, Anizar; Hernadewita, Hernadewita (Jurnal MEKANIKAL, 2013)
Machining process is part of the production process where cutting process of work piece is done by using machine tools. Machine tools are used in the machining process includes lathe machines, milling machines, shaping machines, drilling machines and other machine tools. For a cylindrical work piece the cutting process can be done by using a lathe. Lathe process can make cylindrical objects, holes, taper and other forms. In the cutting process of work piece with a lathe machine are required high accuracy and precision especially for work piece such as shafts , pistons and objects that serve as a connecting other components. Work piece with high accuracy and precision can be obtained by use the reliable of machine tools, cutting condition, the selection of machining elements and material of cutting tools; operators have a skill for operation of machine tools. Cutting conditions such as mounting work pieces that are not center (run out) or overhang of work piece with strong pressure between head stock and tail stock can be resulting deflection. Run out and deflection happened can be cause the cutting force is not uniform. Therefore cause damage to the work piece and machine. Damage on the work piece can be seen from the quality of the cutting (surface roughness) and for machine on the case of chatter or vibration arising from the cutting force. In this paper we will focus to determine the effect of cutting tools material and run out of material on the surface roughness where as machining element used is the depth of cut and feeding. Work piece used is made of medium carbon steel.